The Effect of Problem-Based Learning Model Assisted by Wordwall Application on Student Learning Outcomes in Grade V IPAS Subject - Ardiana, Risma Nur; Rizal, Rizal; Pahriadi, Pahriadi; Zulnuraini, Zulnuraini; Lapasere, Sisriawan (FKIP - Universitas Riau, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model supported by the Wordwall application on student learning outcomes in Grade V IPAS subjects at SD Inpres Kabonena. This research employs a quantitative approach using a pre-experimental design, specifically the one-group pretest-posttest design. The sample consisted of 25 students selected through total sampling. Data were collected through multiple-choice tests, interviews, and documentation. The analysis involved prerequisite tests including normality testing, N-Gain analysis, and hypothesis testing using the Paired Sample T-Test, assisted by IBM SPSS Statistics version 27. The results of this study indicate a T-test significance value of 0.001 < 0.05; therefore, H₀ is rejected and Hₐ is accepted, meaning that there is a significant effect of the Problem-Based Learning model assisted by the Wordwall application on student learning outcomes. It can be concluded that the Problem-Based Learning model assisted by the Wordwall application has a significant effect on the learning outcomes of Grade V students in IPAS subjects at SD Inpres Kabonena. The Problem-Based Learning model assisted by the Wordwall application deserves to be considered as an alternative solution for innovative and effective learning in improving student learning outcomes.